Meningkatkan literasi digital dan keterampilan tekhnologi siswa di SMP Islam Miftahul Ulum - septantiningtyas , Niken; hidayah , Nurul; dia, Nurul Asiyah; roqib, Faizah; zulaiha, Siti (ELEMENTARY : Journal of Primary Education, 2024)
This research aims to explain the efforts made by Miftahul Ulum Islamic Middle School to improve students' digital literacy and information technology skills. Digital literacy and information technology skills have become an important need in today's digital era, where information technology plays a key role in daily life and the development of the world of education. This research uses a qualitative approach with interviews and observation as data collection methods. The research results show that Miftahul Ulum Islamic Middle School has implemented various strategies to improve students' digital literacy and information technology skills. One of the strategies adopted is the integration of technology in the curriculum, where each subject uses technology as a learning tool. Apart from that, the school has also provided extensive internet access and adequate information technology devices for students. Apart from that, Miftahul Ulum Islamic Middle School has also held regular information technology skills training for teachers and students. This helps teachers to understand the technology used in learning and teach students more effectively. Students also receive training to master software and applica relevant to the curriculum. In order to increase digital literacy, this school also places emphasis on media literacy and information literacy. Students are taught to critique the information they encounter in the digital world and understand its impact. This helps students become intelligent and ethical consumers in